Spun-bonded nonwoven fabric, wire pressing tape, printing base material, and method for producing spun-bonded nonwoven fabric

By controlling the temperature range of the crystallization peak and melting peak of spunbond nonwoven fabric and the difference in intrinsic viscosity of core-sheath composite fibers, combined with hot pressing process, the problems of insufficient mechanical strength and surface smoothness of spunbond nonwoven fabric are solved, and high-performance nonwoven fabric suitable for wire wrapping tape and printing substrate is produced.

CN120917196APending Publication Date: 2025-11-07TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480017528.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2024-03-27
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing spunbond nonwoven fabrics, when bonded by heat pressing, lack sufficient mechanical strength and surface smoothness, making it difficult to simultaneously meet the performance requirements of wire wrapping tape and printing substrate.

Method used

By controlling the crystallization peak and melting peak in the differential scanning calorimetry of spunbond nonwoven fabric within a specific temperature range, combined with the intrinsic viscosity difference of core-sheath composite fibers and hot pressing process, spunbond nonwoven fabric with excellent mechanical strength and good surface smoothness can be produced.

Benefits of technology

It achieves a significant improvement in the mechanical strength and surface smoothness of spunbond nonwoven fabrics, making them suitable for wire wrapping tapes and printing substrates, and meeting performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005585109550000171
    Figure BDA0005585109550000171
Patent Text Reader

Abstract

The present invention addresses the problem of providing a non-woven fabric having excellent mechanical strength and excellent surface smoothness. The present invention is a spun-bonded nonwoven fabric comprising fibers mainly composed of a polyethylene terephthalate resin, the spun-bonded nonwoven fabric having a crystallization peak in the range of 100-150 DEG C (inclusive) and a single melting peak in the range of 250-270 DEG C (inclusive) in differential scanning calorimetry, and the maximum height roughness Rz being 40.0 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a spunbond nonwoven fabric, a wire wrapping tape, and a printing substrate. BACKGROUND

[0002] The nonwoven fabric used in the wire wrapping tape requires properties such as tensile strength, surface smoothness that makes it easy to peel off the sheath material, thinness, and the like. In the printing substrate, in addition to mechanical strength, the surface smoothness of the nonwoven fabric is also an important property in terms of the clarity of printing and the uniform adhesion of ink.

[0003] In the past, in the spunbond nonwoven fabric, in order to obtain a nonwoven fabric that is excellent in mechanical strength and surface smoothness, it was not enough to rely on bonding based on heat pressure bonding, and resin processing was required in combination (Patent Document 1, Patent Document 2) because of insufficient strength and smoothness. On the other hand, in order to satisfy these characteristics by bonding using heat pressure bonding alone, various studies have been conducted.

[0004] In Patent Document 3, as a method for obtaining a polyethylene terephthalate spunbond nonwoven fabric suitable as a wire wrapping tape or a printing substrate, a spunbond nonwoven fabric is proposed in which the reduced viscosity of polyethylene terephthalate is increased, the strength of the fiber itself is increased, and a specific flatness and a specific fineness are provided, and high strength and excellent smoothness are achieved.

[0005] In Patent Document 4, a spunbond nonwoven fabric is proposed in which the intrinsic viscosity is within a specific range, and the ratio of the flatness of the fiber surface layer to the inner layer is within a specific range.

[0006] PRIOR ART DOCUMENTS

[0007] PATENT DOCUMENTS

[0008] Patent Document 1: Japanese Patent Application Laid-Open (JP-A) No. 55-32342

[0009] Patent Document 2: Japanese Patent Application Laid-Open (JP-A) No. 57-56564

[0010] Patent Document 3: Japanese Patent Application Laid-Open (JP-A) No. 2001-140157

[0011] Patent Document 4: Japanese Patent Application Laid-Open (JP-A) No. 2007-197891 SUMMARY

[0012] PROBLEMS TO BE SOLVED BY THE INVENTION

[0013] In Patent Document 3, by making the flat yarn, the inter-fiber voids are made small, and the surface smoothness can be improved, but relying on bonding based on heat pressure bonding is not sufficient in terms of strength and smoothness.

[0014] In Patent Literature 4, by making the intrinsic viscosity be in a specific range, the strength of the nonwoven fabric is improved, and by making only the fibers of the surface layer of the nonwoven fabric be flattened, the surface smoothness can also be improved, but the bonding based on heat pressure bonding alone is not sufficient in terms of strength and smoothness.

[0015] Therefore, an object of the present application is to provide a spunbond nonwoven fabric which has mechanical strength by bonding based on heat pressure bonding alone, and which is also excellent in surface smoothness.

[0016] Means for solving the problem

[0017] The present inventors have repeatedly and intensively studied in order to achieve the above object, and as a result, have obtained the insight that by making the crystallization peak and the melting peak in differential scanning calorimetry of a spunbond nonwoven fabric be in a specific temperature range, a spunbond nonwoven fabric which is excellent in mechanical strength and which is also excellent in surface smoothness can be produced. The present application was completed based on the above insight.

[0018] As the present application and the preferred modes thereof, the following configurations are shown.

[0019] [1] A spunbond nonwoven fabric composed of fibers in which a polyethylene terephthalate-based resin is used as a main component, the spunbond nonwoven fabric having a crystallization peak in the range of 100°C or higher and 150°C or lower and a single melting peak in the range of 250°C or higher and 270°C or lower in differential scanning calorimetry, and a maximum height roughness Rz of 40.0 μm or less.

[0020] [2] The spunbond nonwoven fabric according to the above [1], having an apparent density of 0.40 g / cm 3 1.00 g / cm 3 or more.

[0021] [3] An electrical wire wrapping tape comprising the spunbond nonwoven fabric according to the above [1] or [2].

[0022] [4] A printing substrate comprising the spunbond nonwoven fabric according to the above [1] or [2].

[0023] [5] A method for producing a spunbond nonwoven fabric, which is a method for producing the spunbond nonwoven fabric according to the above [1] or [2], sequentially comprising the following steps (a) to (c).

[0024] Process (a): a process of spinning a core-sheath type composite fiber obtained by arranging a low-viscosity polyethylene terephthalate-based resin having an intrinsic viscosity (IV) of 0.05 or more but 0.25 or less lower than that of a high-viscosity polyethylene terephthalate-based resin around the high-viscosity polyethylene terephthalate-based resin having a melting point of 250°C or more but 270°C or less.

[0025] Process (b): a process of drawing and stretching the spun core-sheath type composite fiber with a jet and piling it on a moving web conveyor to form a fiber web.

[0026] Process (c): a process of heat-bonding the fiber web with a flat roll.

[0027] Effects of the Invention

[0028] According to the present application, a nonwoven fabric having excellent mechanical strength and high surface smoothness can be provided. DETAILED DESCRIPTION

[0029] The spun-bond nonwoven fabric of the present application is a spun-bond nonwoven fabric composed of fibers in which a polyethylene terephthalate-based resin is used as a main component, has a crystallization peak in the range of 100°C or more but 150°C or less and a single melting peak in the range of 250°C or more but 270°C or less in differential scanning calorimetry, and has a maximum height roughness Rz of 40.0 μm or less. The following describes the components in detail, but the present application is not limited in any way by the following description as long as the gist of the present application is not deviated from, and various modifications can be made within the scope of the gist of the present application.

[0030] [Polyethylene terephthalate-based resin]

[0031] First, the spun-bond nonwoven fabric of the present application is composed of fibers in which a polyethylene terephthalate-based resin is used as a main component.

[0032] The melting point of the aforementioned polyethylene terephthalate-based resin is preferably 250°C or more but 270°C or less. By making the melting point of the aforementioned polyethylene terephthalate-based resin 250°C or more, heat resistance that can withstand actual use is easily obtained. In addition, by making the melting point of the aforementioned polyethylene terephthalate-based resin 270°C or less, the filaments discharged from the spinneret are easily cooled, and fusion of the fibers to each other is suppressed, and stable spinning is easily performed even for fine fiber diameters. Here, the melting point of the polyethylene terephthalate-based resin refers to the temperature of the largest melting peak obtained by measuring the polyethylene terephthalate-based resin by differential scanning calorimetry (DSC).

[0033] The intrinsic viscosity (IV) of the aforementioned polyethylene terephthalate-based resin is preferably 0.40 or more and 0.70 or less. By making the intrinsic viscosity of the aforementioned polyethylene terephthalate-based resin 0.40 or more, more preferably 0.45 or more, further preferably 0.50 or more, it is possible to suppress a decrease in the strength of the fibers constituting the aforementioned nonwoven fabric. On the other hand, by making the intrinsic viscosity of the aforementioned polyethylene terephthalate-based resin 0.70 or less, it is possible to stably spin even a fine fiber diameter, and to produce a spunbond nonwoven fabric that is uniform in texture and has sufficient strength for practical use.

[0034] In the aforementioned polyethylene terephthalate-based resin, within a range that does not impair the effects of the present application, a crystallization nucleating agent, a matting agent, a lubricant, a pigment, a mildew preventive, an antibacterial agent, a flame retardant, a metal oxide, an aliphatic bisamide and / or an aliphatic monoamide of alkyl-substituted type, and a hydrophilic agent, and the like, can be added. Among these, a metal oxide such as titanium oxide has the following effects: it improves spinnability by reducing the surface friction of the fibers, and prevents fusion of the fibers to each other, and, in addition, when a nonwoven fabric is fusion molded using a hot roll, it improves the fusion property of the nonwoven fabric by increasing the thermal conductivity, and thus it is possible to produce a spunbond nonwoven fabric that is more excellent in mechanical strength.

[0035] [Fiber]

[0036] As the aforementioned fiber constituting the aforementioned nonwoven fabric, a core-sheath type composite fiber is preferable.

[0037] Further, it is preferable that the intrinsic viscosity (IV) of the aforementioned polyethylene terephthalate-based resin of the sheath component be lower than the intrinsic viscosity (IV) of the aforementioned polyethylene terephthalate-based resin of the core component by 0.05 or more and 0.25 or less. Hereinafter, in this manner, the aforementioned polyethylene terephthalate-based resin of the sheath component will be referred to as "low-viscosity polyethylene terephthalate-based resin", and the aforementioned polyethylene terephthalate-based resin of the core component will be referred to as "high-viscosity polyethylene terephthalate-based resin". By making the intrinsic viscosity of the aforementioned low-viscosity polyethylene terephthalate-based resin be 0.05 or more, more preferably 0.08 or more, further preferably 0.10 or more, lower than the intrinsic viscosity of the aforementioned high-viscosity polyethylene terephthalate-based resin, it is possible to concentrate the spinning stress on the core component at the time of spinning, to promote the orientation of the core component, and to suppress the orientation of the sheath component. As a result, it is possible to produce a fiber that is high in single fiber strength and also excellent in thermal adhesion, and thus it is easy to obtain a nonwoven fabric that is excellent in mechanical strength. On the other hand, by making the intrinsic viscosity of the aforementioned low-viscosity polyethylene terephthalate-based resin be 0.25 or less, preferably 0.20 or less, lower than the intrinsic viscosity of the aforementioned high-viscosity polyethylene terephthalate-based resin, it is possible to improve the single fiber strength of the core-sheath type composite fiber.

[0038] Further, the intrinsic viscosity (IV) of the aforementioned high viscosity polyethylene terephthalate-based resin is preferably 0.55 or more and 0.70 or less. By making the intrinsic viscosity of the aforementioned high viscosity polyethylene terephthalate-based resin 0.55 or more, it is possible to prevent a decrease in single fiber strength. Further, by making the intrinsic viscosity of the high viscosity polyethylene terephthalate-based resin 0.70 or less, it is possible to stably spin even a fine fiber diameter, and to produce a spunbond nonwoven fabric that is uniform in texture and has sufficient strength for practical use.

[0039] The mass ratio of the sheath component in the aforementioned core-sheath type composite fiber is preferably 10 mass% or more and 80 mass% or less. By making the mass ratio of the aforementioned sheath component 10 mass% or more, more preferably 15 mass% or more, further preferably 20 mass% or more, it is possible to firmly fuse the sheath components to each other at heat press bonding, and to produce a spunbond nonwoven fabric that has sufficient strength for practical use. On the other hand, by making the ratio of the aforementioned sheath component 80 mass% or less, more preferably 70 mass% or less, further preferably 60 mass% or less, it is possible to increase the proportion of the high-oriented core component, to improve the single fiber strength of the core-sheath type composite fiber, and to produce a spunbond nonwoven fabric that has sufficient strength for practical use.

[0040] The composite form in the aforementioned core-sheath type composite fiber can be, for example, a concentric core-sheath type, an eccentric core-sheath type, an island-in-the-sea type, and the like. Among these, from the aspects of excellent spinnability, the ability to uniformly bond the fibers to each other using heat press bonding, and the ability to produce a spunbond nonwoven fabric that is excellent in mechanical strength, it is preferable to form a composite form of a core-sheath type, and more preferable to form a composite form of a concentric core-sheath type.

[0041] The average fiber diameter of the aforementioned fiber is preferably 6.0 μm or more and 20.0 μm or less. By making the aforementioned average fiber diameter 6.0 μm or more, more preferably 7.0 μm or more, further preferably 8.0 μm or more, it is possible to prevent a decrease in spinnability, to improve production stability, and to produce a spunbond nonwoven fabric that is also excellent in mechanical strength. On the other hand, by making the aforementioned average fiber diameter 20.0 μm or less, more preferably 18.0 μm or less, further preferably 16.0 μm or less, it is possible to produce a spunbond nonwoven fabric that is uniform in texture and has sufficient strength for practical use.

[0042] In the present application, the average fiber diameter (μm) is the value obtained by the following method.

[0043] (i) Randomly collect 10 small pieces of 10 mm x 10 mm from the spunbond nonwoven fabric.

[0044] (ii) Using a scanning electron microscope or the like, a photograph capable of measuring fiber thickness is taken at a magnification of 500 to 2,000 times with respect to the surface of the collected small piece sample.

[0045] (iii) From the photograph taken for each small piece sample, 100 fibers are arbitrarily selected by 10, and the thicknesses thereof are measured. Assuming that the cross section of the fiber is circular, the thickness is taken as the fiber diameter.

[0046] (iv) The value obtained by rounding off the second decimal place of the arithmetic mean of the fiber diameters to the nearest integer is taken as the average fiber diameter.

[0047] [Spunbonded nonwoven fabric]

[0048] The spunbonded nonwoven fabric of the present application has a crystallization peak in the range of 100°C or higher and 150°C or lower in differential scanning calorimetry. By having the aforementioned spunbonded nonwoven fabric have a crystallization peak temperature in the above range, fusion of fibers to each other at the time of flat roll bonding is promoted, resulting in a spunbonded nonwoven fabric excellent in smoothness of the nonwoven fabric surface and also excellent in mechanical strength. On the other hand, in the case of a spunbonded nonwoven fabric having no crystallization peak, not only is fusion of fibers to each other difficult to occur and the smoothness of the nonwoven fabric surface is low, but also the spunbonded nonwoven fabric is low in mechanical strength.

[0049] Further, the aforementioned spunbonded nonwoven fabric has a single melting peak in the range of 250°C or higher and 270°C or lower in differential scanning calorimetry. By having a single melting peak in the above range, the problem of low-melting-point components being fused and adhering to a hot roll or the like at the time of heat bonding does not occur, and fibers can be firmly heat-bonded to each other at a sufficient temperature, so that a spunbonded nonwoven fabric having a strength sufficient for practical use is obtained.

[0050] Here, the temperature Tc (°C) of the crystallization peak and the temperature Tm (°C) of the melting peak of the spunbonded nonwoven fabric are values calculated by the following steps from those obtained by differential scanning calorimetry (DSC).

[0051] (i) A small piece of the spunbonded nonwoven fabric is sampled in an amount of 0.5 mg to 5 mg.

[0052] (ii) Using differential scanning calorimetry (DSC), a DSC curve is obtained by raising the temperature from room temperature to 280°C at a temperature raising rate of 16°C / minute.

[0053] (iii) The peak top temperature of the crystallization exothermic peak is read from the DSC curve, and taken as the temperature Tc (°C) of the crystallization peak of the spunbonded nonwoven fabric. The peak top temperature of the melting endothermic peak is read, and taken as the temperature Tm (°C) of the melting peak of the spunbonded nonwoven fabric.

[0054] The maximum height roughness Rz of the aforementioned spunbond nonwoven fabric is 40.0 μm or less. By making the maximum height roughness Rz 40.0 μm or less, preferably 35.0 μm or less, further preferably 33.0 μm or less, it is possible to eliminate local unevenness from the surface of the nonwoven fabric, and a nonwoven fabric having excellent smoothness of the surface can be produced.

[0055] Note that, in the present application, the maximum height roughness Rz is a value determined / calculated using the following method.

[0056] (i) A 10 cm x 10 cm long fiber nonwoven fabric is arbitrarily collected at 10.

[0057] (ii) In the arbitrarily collected nonwoven fabric, using a surface roughness meter (for example, "Surftest SJ-210" manufactured by Mitutoyo Corporation), in accordance with the standards of JIS B0610:2001 "Geometrical Product Specifications (GPS) - Surface Texture: Profile Method - Nominal Characteristics of Abrasive Cut-off Waviness", measurement is performed on a range of 21 mm in the width direction of the long fiber nonwoven fabric sheet under conditions of λc = 2.5 mm, λs = 8 μm, and a measurement speed of 0.5 mm / s, and the maximum height roughness Rz is determined for 10 points in units of 0.1 μm on each surface of each collected sample.

[0058] (iii) The arithmetic mean of the aforementioned determined values is calculated on each surface, the second digit after the decimal point is rounded, and the value of the surface having the higher value is taken as the maximum height roughness Rz.

[0059] The arithmetic mean roughness Ra of the spunbond nonwoven fabric of the present application is preferably 4.5 μm or less. By making the arithmetic mean roughness Ra 4.5 μm or less, more preferably 4.0 μm or less, further preferably 3.5 μm or less, the entire surface of the nonwoven fabric becomes smooth, and a nonwoven fabric having excellent smoothness can be produced.

[0060] In the present application, the arithmetic mean roughness Ra is a value determined / calculated using the following method.

[0061] (i) A 10 cm x 10 cm long fiber nonwoven fabric is arbitrarily collected at 10.

[0062] (ii) In any of the collected nonwoven fabrics, using a surface roughness meter (for example, "Surftest SJ-210" manufactured by Mitutoyo Corporation), in accordance with the standards of JIS B0610:2001 "Geometrical Product Specifications (GPS) - Surface Texture: Profile Method - Nominal Characteristics of Abrasive Cut-off Specimens", under the conditions of λc = 2.5 mm, λs = 8 μm, and a measurement speed of 0.5 mm / s, the range of 21 mm in the width direction of the fibrous nonwoven fabric sheet was measured, and for each of the collected samples, the arithmetic average roughness Ra of 10 points was measured in units of 0.1 μm for each surface.

[0063] (iii) For the values (total of 20 points) of the two surfaces measured above, the arithmetic mean was calculated, and the second digit after the decimal point was rounded off to the nearest whole number as the arithmetic average roughness Ra.

[0064] The tensile strength per unit area weight of the spunbond nonwoven fabric of the present application is preferably 5.00 (N / 5 cm) / (g / m 2 ) or more. By making the tensile strength 5.00 (N / 5 cm) / (g / m 2 ) or more, more preferably 5.50 (N / 5 cm) / (g / m 2 ) or more, and further preferably 5.80 (N / 5 cm) / (g / m 2 ) or more, the minimum tensile strength can be obtained, and thus it is preferable.

[0065] In the present application, the tensile strength per unit area weight of the spunbond nonwoven fabric ((N / 5 cm) / (g / m 2 ) is a value calculated in accordance with 6.3 "Tensile strength and elongation" of JIS L1913:2010 "Test methods for general purpose fibrous nonwoven fabrics" using the following method.

[0066] (i) From the nonwoven fabric, three samples of 30 cm x 5.0 cm in width were collected at equal intervals in the length direction (MD) and the width direction (CD), respectively.

[0067] (ii) Under the conditions of a clamping interval of 20 cm and a tensile speed of 100 ± 10 mm / min, a load was applied until the sample was cut.

[0068] (iii) The strength of the sample at the maximum load was taken as the tensile strength (N / 5 cm), and the average value of the three points in MD and CD was calculated, and the total of the respective average values was taken as the tensile strength of the spunbond nonwoven fabric.

[0069] (iv) The tensile strength per unit area weight of the spunbond nonwoven fabric ((N / 5 cm) / (g / m 2)) Round off the third digit after the decimal point.

[0070] Tensile strength per unit area weight of spunbond non-woven fabric ((N / 5cm) / (g / m 2 )) = [Tensile strength of spunbond non-woven fabric (N / 5cm)] / Unit area weight (g / m 2 ).

[0071] The apparent density of the spunbond non-woven fabric of the present invention is preferably 0.40 g / cm 3 or more and 1.00 g / cm 3 or less. By making the apparent density 0.40 g / cm 3 or more, preferably 0.42 g / cm 3 or more, more preferably 0.45 g / cm 3 or more, a spunbond non-woven fabric having both thinness and mechanical strength can be produced. In addition, by making the apparent density 1.00 g / cm 3 or less, preferably 0.95 g / cm 3 or less, more preferably 0.90 g / cm 3 or less, it can have a certain air permeability. For example, when used as a printing substrate, the ink can easily penetrate into the interior of the non-woven fabric, so it is preferred.

[0072] It should be noted that the apparent density (g / cm 3 ) of the aforementioned spunbond non-woven fabric adopts the following value: After dividing the unit area weight (g / m 2 ) of the spunbond non-woven fabric described below by the thickness (mm) of the spunbond non-woven fabric described below and performing unit conversion, the third digit after the decimal point of the result (g / cm 3 ) is rounded off to calculate the value. Here, for the thickness (mm) of the spunbond non-woven fabric, it is calculated through the following steps.

[0073] (i) Collect 3 pieces of spunbond non-woven fabric with a width of 10 cm in the length direction.

[0074] (ii) Using a punch with a diameter of 10 mm (Japanese: 加圧子), measure the thickness at 10 points at intervals of 1 m in the width direction of the spunbond non-woven fabric at a load of 10 kPa in units of 0.01 mm.

[0075] (iii) Calculate the arithmetic mean of the measured values obtained above for each of the 3 pieces of spunbond non-woven fabric collected, and further round off the third digit after the decimal point of the arithmetic mean for the 3 pieces of spunbond non-woven fabric to calculate.

[0076] It should be noted that the unit area weight (g / m 2 ) of the aforementioned spunbond non-woven fabric is calculated through the following steps.

[0077] (i) Collect 3 pieces of spun-bonded nonwoven fabric of 30 cm x 50 cm.

[0078] (ii) Measure the mass of each sample, respectively, and calculate the average value of the obtained values as the mass per unit area (g / m 2 ), rounding off the first digit after the decimal point, to obtain the weight per unit area.

[0079] [Method for manufacturing spun-bonded nonwoven fabric]

[0080] The spun-bonded nonwoven fabric of the present application can be suitably manufactured by the method for manufacturing spun-bonded nonwoven fabric of the present application. That is, the method for manufacturing spun-bonded nonwoven fabric of the present application is a method for manufacturing the spun-bonded nonwoven fabric of the present application, and sequentially includes the following steps (a) to (c).

[0081] [Step (a): Step of spinning fiber]

[0082] In step (a), a core-sheath type composite fiber is spun, which is obtained by arranging a low-viscosity polyethylene terephthalate-based resin having an intrinsic viscosity (IV) of 0.05 or more but 0.25 or less lower than that of the aforementioned high-viscosity polyethylene terephthalate-based resin around a high-viscosity polyethylene terephthalate-based resin having a melting point of 250°C or more but 270°C or less.

[0083] That is, in the aforementioned core-sheath type composite fiber, it is preferable to use the aforementioned high-viscosity polyethylene terephthalate-based resin as the core component and the aforementioned low-viscosity polyethylene terephthalate-based resin as the sheath component. By making the difference between the intrinsic viscosity of the aforementioned core component and the intrinsic viscosity of the aforementioned sheath component 0.05 or more, and more preferably 0.10 or more, it is possible to concentrate the spinning stress on the aforementioned core component at the time of spinning, promote the orientation of the aforementioned core component, and suppress the orientation of the aforementioned sheath component. On the other hand, by making the difference between the intrinsic viscosity of the aforementioned core component and the intrinsic viscosity of the aforementioned sheath component 0.25 or less, and preferably 0.20 or less, it is possible to improve the single fiber strength of the aforementioned core-sheath type composite fiber, and suppress the sharp softening at the time of heat pressure bonding, and also suppress the sticking to the heat roll at the time of manufacturing.

[0084] The aforementioned core-sheath type composite fiber is preferably melted at a temperature of the melting point or more but the melting point + 70°C or less, and is melt-extruded from a spinneret at a temperature of the melting point or more but the melting point + 70°C.

[0085] The shape of the discharge hole of the spinneret from which the aforementioned core-sheath type composite fiber is extruded can be circular, elliptical, polygonal, polylobed, or a combination thereof, corresponding to the cross-sectional shape of the aforementioned fiber. Among these, the circular shape is more preferable from the viewpoint of efficiently obtaining points at which the fibers adhere to each other and firmly adhering the fibers to each other by thermal bonding.

[0086] [Process (b): Process of forming a fiber web]

[0087] In process (b), the spun aforementioned core-sheath type composite fiber is drawn, stretched, and accumulated on a moving web conveyor by a jet to form a fiber web.

[0088] In process (b), the spun aforementioned fiber is preferably drawn, stretched, and accumulated on a moving web conveyor by a jet to form a fiber web. At this time, the spinning speed at which the fiber is drawn is preferably 3000 m / min or more and 6000 m / min or less.

[0089] [Process (c): Process of thermally bonding the fiber web]

[0090] In process (c), the aforementioned fiber web is thermally bonded by a flat roller.

[0091] By thermally bonding the aforementioned fiber web, a desired spunbond nonwoven fabric can be obtained.

[0092] The method of thermally bonding the aforementioned fiber web is performed using a pair of flat rollers. By thermally bonding using a flat roller, unlike bonding using an embossed roller, the local irregularities disappear, the maximum height roughness of the surface can be reduced, and a nonwoven fabric having excellent surface smoothness can be produced.

[0093] As the surface material of the aforementioned flat roller, it is preferable to use a pair of metal rollers in order to obtain sufficient thermal bonding effects.

[0094] The surface temperature of the aforementioned flat roller at the time of thermal bonding is preferably set to a temperature that is 10°C to 100°C lower than the melting point (hereinafter, sometimes referred to as Tm (°C)) of the polyethylene terephthalate-based resin used (i.e., (Tm-100) °C to (Tm-10) °C). By setting the surface temperature of the hot roller to (Tm-100) °C or more, and more preferably (Tm-90) °C or more, a spunbond nonwoven fabric having a strength that is suitable for practical use can be obtained by moderately thermally bonding. In addition, by setting the surface temperature of the flat roller to (Tm-10) °C or less, and more preferably (Tm-15) °C or less, excessive thermal bonding can be suppressed, and the spunbond nonwoven fabric can be inhibited from becoming partially film-like.

[0095] The linear pressure of the aforementioned flat roller at the time of thermal compression bonding is preferably 90 N / cm or more and 1000 N / cm or less. By setting the linear pressure for thermal compression bonding to 90 N / cm or more, a spunbond nonwoven fabric having excellent mechanical strength can be produced. By setting the linear pressure for thermal compression bonding to 1000 N / cm or less, excessive fusion of fibers to each other can be prevented.

[0096] [Wire pressing tape]

[0097] The wire pressing tape of the present application contains the aforementioned nonwoven fabric. In this way, a wire pressing tape having thinness and good mechanical strength and also excellent surface smoothness can be produced. The wire pressing tape referred to in the present application is a tape that is disposed between an electric wire cable and a sheath covering the cable and that presses the aforementioned electric wire cable. In order to impart functions such as semiconductivity and water absorbency to the nonwoven fabric, the wire pressing tape of the present application can also be subjected to post-processing.

[0098] The use of the wire pressing tape of the present application is not particularly limited and can be used in various fields. As examples of the use of the wire pressing tape of the present application, specifically, power cable for power transmission, communication cable, and the like can be given.

[0099] [Printed substrate]

[0100] The printed substrate of the present application contains the aforementioned nonwoven fabric. In this way, a printed substrate having excellent mechanical strength and also good surface smoothness and excellent printability can be produced. As the printed substrate, for example, a substrate for commercial printing such as inkjet printing, laser printing, flexographic printing, letterpress printing, gravure printing, offset printing, thermal transfer printing, and the like is preferred. In order to impart functions such as flame retardancy and concealment, the printed substrate of the present application can also be subjected to post-processing.

[0101] The use of the printed substrate of the present application is not particularly limited and can be used in various fields. As examples of the use of the printed substrate of the present application, specifically, wallpaper, posters, labels, and the like can be given.

[0102] Examples

[0103] Next, the nonwoven fabric of the present application will be described specifically based on the examples. However, the present application is not limited only to these examples.

[0104] [Measurement method]

[0105] The evaluation methods used in the examples and the measurement conditions thereof will be described. Note that in the measurement of each property, the measurement was performed based on the aforementioned method unless otherwise specified.

[0106] (1) Melting point (°C) of polyethylene terephthalate-based resin

[0107] The melting point was determined as the temperature at which an extreme was provided in the melting endotherm curve obtained using a differential scanning calorimeter (DSC-2 manufactured by PerkinElmer Co., Ltd.) at a temperature increase rate of 16°C / min.

[0108] (2) Intrinsic viscosity (IV) of the polyethylene terephthalate-based resin

[0109] The intrinsic viscosity (IV) of the polyethylene terephthalate-based resin was determined using the following method.

[0110] In 100 mL of o-chlorophenol, 8 g of the sample was dissolved, and the relative viscosity η was calculated using the following formula using an Ostwald viscometer at a temperature of 25°C. r .

[0111] η r = η / η0= (t x d) / (t0 x d0)

[0112] Here, η represents the viscosity of the polymer solution, η0represents the viscosity of o-chlorophenol, t represents the falling time (seconds) of the solution, d represents the density (g / cm 3 ) of the solution, t0represents the falling time (seconds) of o-chlorophenol, and d0represents the density (g / cm 3 ) of o-chlorophenol.

[0113] Next, the intrinsic viscosity (IV) was calculated from the relative viscosity η r using the following formula.

[0114] Intrinsic viscosity (IV) = 0.0242 η r + 0.2634.

[0115] (3) Average fiber diameter of the fiber (μm)

[0116] The average fiber diameter of the fiber was calculated using the aforementioned method using a scanning electron microscope (VHX-D500 manufactured by Keyence Co., Ltd.) as the scanning electron microscope.

[0117] (4) Temperature of the crystallization peak (Tc) of the spunbond nonwoven fabric

[0118] The temperature of the crystallization peak of the spunbond nonwoven fabric was calculated using the aforementioned method using a differential scanning calorimeter (DSC-2 manufactured by PerkinElmer Co., Ltd.) as the differential scanning calorimeter.

[0119] (5) Temperature of the melting peak (Tm) of the spunbond nonwoven fabric

[0120] As for the melting peak temperature of the spunbond nonwoven fabric, a "DSC-2" manufactured by PerkinElmer Co. was used as a differential scanning calorimeter, and the aforementioned method was used for the calculation.

[0121] (6) Surface maximum height roughness Rz (μm) of the spunbond nonwoven fabric

[0122] As for the surface maximum height roughness of the spunbond nonwoven fabric, a "Surftest SJ-210" manufactured by Mitutoyo Corporation was used as a surface roughness meter, and the aforementioned method was used for the calculation.

[0123] (7) Weight per unit area (g / m2) of the spunbond nonwoven fabric 2 )

[0124] The weight per unit area of the spunbond nonwoven fabric was calculated using the aforementioned method.

[0125] (8) Thickness (mm) of the spunbond nonwoven fabric

[0126] The thickness of the spunbond nonwoven fabric was calculated using the aforementioned method.

[0127] (9) Apparent density (g / cm3) of the spunbond nonwoven fabric 3 )

[0128] The apparent density of the spunbond nonwoven fabric was calculated using the aforementioned method.

[0129] (10) Tensile strength per unit weight (N / 5 cm) / (g / m2) of the spunbond nonwoven fabric 2 )

[0130] As for the tensile strength per unit weight of the spunbond nonwoven fabric, an "RTG-1250" manufactured by Baldwin Co. was used, and the aforementioned method was used for the measurement.

[0131] (11) Surface arithmetic mean roughness Ra (μm) of the spunbond nonwoven fabric

[0132] As for the surface arithmetic mean roughness Ra of the spunbond nonwoven fabric, a "Surftest SJ-210" manufactured by Mitutoyo Corporation was used as a surface roughness meter, and the aforementioned method was used for the measurement.

[0133] [Resins used]

[0134] For the resins used in the examples and comparative examples, the detailed contents thereof are described below.

[0135] • Polyethylene terephthalate-based resin A (PET_A): polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.65, and a melting point of 255°C.

[0136] • Polyethylene terephthalate-based resin B (PET_B): polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.51, and a melting point of 255°C.

[0137] • Polyethylene terephthalate-based resin C (PET_C): polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.70, and a melting point of 255°C.

[0138] • Polyethylene terephthalate-based resin D (PET_D): polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.56, and a melting point of 255°C.

[0139] • Polyethylene terephthalate-based resin E (PET_E): polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.45, and a melting point of 255°C.

[0140] • Polyethylene terephthalate-based resin F (PET_F): polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.62, and a melting point of 255°C.

[0141] • Polyethylene terephthalate-based resin G (CO-PET): copolymerized polyethylene terephthalate having a moisture content dried to 50 mass ppm or less, an intrinsic viscosity (IV) of 0.64, a copolymerization rate of isophthalic acid of 11 mol%, and a melting point of 230°C.

[0142] [Example 1]

[0143] (Process of Spinning Fiber)

[0144] Polyethylene terephthalate-based resin A and polyethylene terephthalate-based resin B were each melted at a temperature of 295°C. Subsequently, with polyethylene terephthalate-based resin A as a core component and polyethylene terephthalate-based resin B as a sheath component, a concentric core-sheath type composite fiber was spun from a circular discharge hole at a spinneret temperature of 295°C, with the weight ratio of core : sheath set to 80 : 20.

[0145] (Process of Forming Fiber Web)

[0146] The fiber spun by the above procedure was drawn at a spinning speed of 5000 m / min to be accumulated on a web conveyor whose moving speed was adjusted in such a manner that the weight per unit area of the obtained nonwoven fabric became 35.0 g / m 2 The web conveyor whose moving speed was adjusted in such a manner that the weight per unit area of the obtained nonwoven fabric became 35.0 g / m

[0147] (Procedure of heat-bonding the fiber web)

[0148] Next, the formed fiber web was heat-bonded using a pair of upper and lower heat flat rolls composed of an upper roll and a lower roll, under conditions of a surface temperature of the heat flat roll: 180°C, and a line pressure: 686 N / cm, to obtain a spunbond nonwoven fabric.

[0149] Upper roll: metal flat roll

[0150] Lower roll: metal flat roll.

[0151] The results of evaluation of the obtained spunbond nonwoven fabric are shown in Table 1.

[0152] [Example 2]

[0153] In the procedure of spinning the fiber, polyethylene terephthalate-based resin A was replaced by polyethylene terephthalate-based resin C. Except for this, the same procedure and conditions as in Example 1 were used to obtain a spunbond nonwoven fabric. The physical properties of the obtained spunbond nonwoven fabric are shown in Table 1.

[0154] [Example 3]

[0155] In the procedure of spinning the fiber, polyethylene terephthalate-based resin A was replaced by polyethylene terephthalate-based resin D. Except for this, the same procedure and conditions as in Example 1 were used to obtain a spunbond nonwoven fabric. The physical properties of the obtained spunbond nonwoven fabric are shown in Table 1.

[0156] [Example 4]

[0157] In the procedure of spinning the fiber, polyethylene terephthalate-based resin B was replaced by polyethylene terephthalate-based resin E. Except for this, the same procedure and conditions as in Example 2 were used to obtain a spunbond nonwoven fabric. The physical properties of the obtained spunbond nonwoven fabric are shown in Table 1.

[0158] [Comparative Example 1]

[0159] In the process of spinning the fibers, polyethylene terephthalate-based resin B was made into polyethylene terephthalate-based resin A, and a single-component fiber was produced. In the process of heat-bonding the fiber web, the surface temperature of the flat metal roll was made to be 250°C. Other than this, the same procedure and conditions as in Example 1 were used to produce a spun-bonded nonwoven fabric. The physical properties of the obtained spun-bonded nonwoven fabric are shown in Table 1.

[0160] [Comparative Example 2]

[0161] In the process of spinning the fibers, polyethylene terephthalate-based resin B was replaced with polyethylene terephthalate-based resin G. Other than this, the same procedure and conditions as in Example 1 were used to produce a spun-bonded nonwoven fabric. The physical properties of the obtained spun-bonded nonwoven fabric are shown in Table 1.

[0162] [Comparative Example 3]

[0163] In the process of spinning the fibers, polyethylene terephthalate-based resin B was replaced with polyethylene terephthalate-based resin F. Other than this, the same procedure and conditions as in Example 1 were used to produce a spun-bonded nonwoven fabric. The physical properties of the obtained spun-bonded nonwoven fabric are shown in Table 1.

[0164] [Comparative Example 4]

[0165] In the process of heat-bonding the fiber web, the upper roll was replaced from a flat metal roll to a round knurling roll made of metal (bonding rate 16%). Other than this, the same procedure and conditions as in Example 1 were used to produce a spun-bonded nonwoven fabric. The physical properties of the obtained spun-bonded nonwoven fabric are shown in Table 1.

[0166] [Table 1]

[0167]

[0168] As for the spun-bonded nonwoven fabrics of Examples 1 to 4, the tensile strength was high, the mechanical strength was excellent, and the arithmetic average roughness Ra was also low, and the surface smoothness was excellent.

[0169] On the other hand, as for the spun-bonded nonwoven fabrics of Comparative Examples 1 to 4, the arithmetic average roughness Ra was high and the surface smoothness was not excellent (Comparative Examples 1 to 4), and the tensile strength was low and the mechanical strength was insufficient (Comparative Example 1).

Claims

1. A spunbond nonwoven fabric which is a spunbond nonwoven fabric composed of fibers of which a polyethylene terephthalate-based resin is a main component, the spunbond nonwoven fabric having a crystallization peak in a range of 100°C or higher and 150°C or lower and a single melting peak in a range of 250°C or higher and 270°C or lower in differential scanning calorimetry, and a maximum height roughness Rz of 40.0 μm or less.

2. The spunbond nonwoven fabric according to claim 1, having an apparent density of 0.40 g / cm 3 The above 1.00 g / cm 3 The below.

3. An electrical wire wrapping tape comprising the spunbond nonwoven fabric according to claim 1 or 2.

4. A printing substrate comprising the spunbond nonwoven fabric according to claim 1 or 2.

5. A method for producing a spunbond nonwoven fabric, which is a method for producing the spunbond nonwoven fabric according to claim 1 or 2, sequentially comprising the following steps (a) to (c), Step (a): a step of spinning a core-sheath type composite fiber obtained by disposing a low-viscosity polyethylene terephthalate-based resin having an intrinsic viscosity (IV) of 0.05 or more and 0.25 or less lower than an intrinsic viscosity (IV) of a high-viscosity polyethylene terephthalate-based resin around the high-viscosity polyethylene terephthalate-based resin having a melting point of 250°C or higher and 270°C or lower; Step (b): a step of drawing and stretching the spun core-sheath type composite fiber by means of a spinner and piling it on a moving web conveyor to form a fiber web; Step (c): a step of heat-bonding the fiber web by means of a flat roll.

Citation Information

Patent Citations

  • Polyester long fiber nonnwoven fabric for pressswinding electric cable and method of manufacturing same

    JP1980032342A

  • Production of polyester long fiber nonwoven fabric for press winding electric cable

    JP1982056564A

  • Spun-bond nonwoven fabric

    JP2001140157A

  • Spun-bond nonwoven fabric

    JP2007197891A